An Investigation of Students' Interest in Learning English Pop Songs at SMAN 4 Wajo - Sahrina Ahmad; Andi Sadapotto; Nurul Faradillah; Ibrahim Manda; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigated the level of tenth-grade students' interest in learning English through English pop songs at SMAN 4 Wajo and identified the internal and external factors influencing that interest. The research employed an integrated mixed-method design. Quantitative data were collected through a 12-item questionnaire organized around four indicators: feeling of enjoyment, students' interest, acceptance, and students' engagement. Qualitative data were obtained through semi-structured interviews with selected students and classroom observations. Questionnaire data were analyzed using score percentages and interest-level categories, while qualitative data were analyzed through data reduction, data display, conclusion drawing and verification, and triangulation. The results showed a total questionnaire score of 694 out of a maximum of 840, producing an overall percentage of 82.62%, which was categorized as high. Feeling of enjoyment contributed the largest share of the total score (186; 26.80%), followed by acceptance (171; 24.64%), students' interest (170; 24.50%), and students' engagement (167; 24.06%). Qualitative findings identified four internal factors - enjoyment, motivation, curiosity about lyrics and vocabulary, and personal preference for pop songs - and two external factors - teachers and learning activities, and accessibility through social media and digital platforms. These findings indicate that English pop songs can provide an enjoyable and relevant learning medium that supports students' interest, motivation, and participation in English learning.